From Painters to Pirates: A Study of Non-Binary Protagonists in Young Adult Fiction - Alex Henderson (International Journal of Young Adult Literature, 2022)
Non-binary gender is a marginalised queer identity increasingly receiving mainstream media representation, a subject that warrants investigation. Non-binary is an umbrella term under which many experiences of gender fall, a factor that necessitates a nuanced variety of narrative representations to avoid perpetuating or creating static and singular archetypes. This article examines a sample of young adult novels with non-binary protagonists published between 2017 and 2020, exploring the various ways these texts express and explore their central characters’ gender identity. My findings reveal thematic commonalities between these novels, with particular focus on the language used to describe these characters’ felt sense of gender, their experiences with dysphoria/euphoria, their relationships to broader queer communities within their story worlds, and the intersections of queer gender and speculative elements. I argue that this subset we might call ‘non-binary YA’ serves as an emblem of the development of queer YA overall, its rapid expansion through various genres and narrative types providing a microcosm of the growth of the literary field and pointing to its future.